Pengaruh Kualitas Produk, Harga, serta Promosi terhadap Keputusan Pembelian Sepeda Motor Yamaha Deta Jogja - Isnanda Yusuf Widagdo; Rinaldi Rinaldi (Jurnal Syntax Admiration, 2024)
Yamaha Deta Jogja as a dealer faces challenges in attracting customers due to increasingly tight competition. This study aims to analyze the effect of product quality, price, and promotion on motorcycle purchasing decisions at Yamaha Deta Jogja. This study uses a quantitative method with data analysis techniques in the form of multiple linear regression. This study found that quality, price, promotion partially and simultaneously have a positive effect on motorcycle purchasing decisions at Yamaha Deta Jogja. Each of these variables shows a significant contribution to consumer decisions in choosing a product, where product quality determines attractiveness based on its durability and reliability. Prices that are in accordance with consumer perceptions are also an important factor, where the match between price and value received increases consumer desire to buy. Effective promotions, through various communication strategies carried out by the company, have succeeded in attracting consumer attention and influencing purchasing decisions.